Engine valve guide pipe as well as preparation process and application thereof
By using Fe-based powder metallurgical materials and TWIP steel powder on the valve conduit of hydrogen fuel engines, combined with magnetron sputtering and multi-stage sintering technology, the wear and corrosion problems of valve conduit in high temperature environments are solved, and a valve conduit with high hardness, easy cutting and high wear resistance is achieved, extending the service life and improving the resistance to hydrogen corrosion.
Patent Information
- Application Number
- CN202411969181.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
In special fuel engines such as hydrogen fuel engines, valve conduits are prone to wear, deformation, burning, and even failure of fracture in complex environments such as high temperature, wear and corrosion, and the existing Fe-based alloy materials have shortcomings in processing difficulty and durability.
Fe-based powder metallurgical material is used to process the working surface of the valve conduit through magnetron sputtering process. The alloy matrix contains elements such as C, N, Co, Cr, Ni, W, Ti, Mn, Al, Cu, V, S, Mo, Mg, Nb and Si, and TWIP steel powder is added as a toughening cutting additive. Temperature press forming, multi-stage sintering and siphon copper seepage are used to improve the hardness, toughness and wear resistance of the material.
The valve conduit is achieved with high hardness, easy cutting, high wear resistance and good high temperature performance, extending service life and improving resistance to hydrogen corrosion and oxidation.
Smart Images

Figure CN119640157A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of powder metallurgy manufacturing of key engine parts for automobiles, ships and large equipment, and particularly relates to a high temperature resistant, easy cutting, highly corrosion resistant and highly wear resistant engine valve guide and its preparation process and application. Background Art
[0002] The automobile industry is a pillar industry in my country. In recent years, with the advancement of my country's dual carbon work, traditional automobile low-emission technology and new energy vehicles have achieved remarkable development. From July 1, 2023, the National VI Emission Standard 6b will be fully implemented nationwide, and the emission level is basically the same as that of developed countries in Europe and the United States. On the basis of the rapid development of lithium battery electric vehicles, my country is actively promoting other new energy vehicle industries, including zero-emission hydrogen and methanol internal combustion engine vehicles.
[0003] Against the above background, my country's new energy vehicle industry has entered a critical development node from quantitative change to qualitative change. The country has included hydrogen internal combustion engines in the hydrogen energy development strategy and encouraged the research and development of hydrogen and methanol engines and vehicles. It is reported that FAW has completed the development of hydrogen engines, and manufacturers such as Changan, GAC, Great Wall, and Geely are also actively carrying out preliminary research and development. It can be expected that a large number of new energy vehicles fueled by hydrogen and methanol will be launched in the near future, providing new quality productivity for the comprehensive realization of low emissions and zero emissions. In addition to important applications in the automotive industry, special fuel internal combustion engines also have broad application prospects in aerospace, shipbuilding, weapons and equipment, and energy.
[0004] Special fuel vehicles (methanol and hydrogen fuel vehicles) need to break through a series of key technologies to achieve comprehensive and large-scale application due to the physical and chemical properties of the fuel itself as well as extremely high hardware conditions and technical requirements.
[0005] When using special fuels (methanol, hydrogen, etc.), the engine needs high compression ratio combustion, high pressure direct injection, special supercharging and other systems. The complexity, control difficulty and reliability of these systems are much higher than those of lithium battery electric vehicles.
[0006] The explosion limit of hydrogen is extremely wide (4.0%-75.6%, while natural gas is only 5%-15%) and the escape and diffusion speed is very fast. It is very easy to ignite and explode, and the explosion range is very wide. Complex control is required from hydrogen storage, transportation pipelines to intake and exhaust, and afterburning and lack of fire may cause deflagration and damage to the exhaust system.
[0007] Hydrogen has active chemical properties and is prone to physical and chemical reactions with most metals, resulting in the so-called "hydrogen embrittlement" phenomenon. Hydrogen can directly produce hydrogen embrittlement when it comes into contact with steel materials without heating or pressurization. Therefore, metal parts such as the engine airway, combustion chamber, piston, valve, valve seat ring, and valve guide must be designed and treated to prevent "hydrogen embrittlement". The valve guide and valve are one of the important friction pairs of the engine. The function of the valve guide is to control the entry of fuel gas and the discharge of exhaust gas. The valve guide and valve cooperate to seal the combustion chamber to reduce the wear of the valve, withstand the impact and wear of the valve in the high temperature environment; as well as the erosion and oxidation of the intake and exhaust flow, that is, when serving at high temperatures, it not only has to withstand high temperature and high stress impact, but also has to be corroded by exhaust gas, which is very easy to cause wear, deformation, burning, and even fracture failure. The valve guide is one of the vulnerable parts of the engine. When it is severely worn, it will cause the valve to sink too much and the airtightness to be poor, which will cause failure and damage. The quality, performance and reliability of the valve guide directly affect the fuel consumption, power, efficiency and service life of the engine.
[0008] At present, the core technology of high-end high-temperature resistant, easy-to-cut, high-corrosion-resistant and high-wear-resistant Fe-based alloy materials for both traditional fuel engines and hydrogen engines is still monopolized by Western developed countries such as Japan, the United States and Germany. Compared with them, the comprehensive performance of similar materials independently developed by my country and related valve guides and other products is still far behind, and high-end products are still completely dependent on imports. Breaking through the technological blockade of Western countries is one of the important issues facing my country's industry. Summary of the invention
[0009] In view of the harsh working environment requirements faced by valve guides in special fuel engines such as hydrogen fuel engines and high-performance engines, as well as the insufficient performance of valve guides in corresponding engines, the present invention aims to invent a high-temperature resistant, easy-to-cut, highly corrosion-resistant and highly wear-resistant Fe-based powder metallurgy material and its preparation process, as well as an engine valve guide made of the material. The material contains alloy elements such as C, N, Co, Cr, Ni, W, Ti, Mn, Al, Cu, V, S, Mo, Mg, Nb and Si, and is suitable for engines of hydrogen fuel vehicles, special fuel vehicles, high-performance vehicles, military heavy equipment and large ships.
[0010] The present invention mainly aims at the working environment and required working performance of the valve guide, re-studies and designs a Fe-based powder metallurgy material composition, and obtains the preparation technology of the Fe-based powder metallurgy material and the corresponding valve guide, which solves the problems of high temperature, wear and corrosion of the valve guide caused by high speed, high temperature and repeated impact in the engine. In particular, the addition of a special toughening and cutting additive solves the problem of difficult cutting of high-hardness materials, reduces the difficulty of processing the valve guide, and prolongs the service life of the valve guide.
[0011] One object of the present invention is to provide an engine valve guide, which is made of an Fe-based alloy substrate and a coating is applied to the working surface of the substrate by a magnetron sputtering process. Among them, the Fe-based alloy matrix is composed of the following components in proportion by mass: C: 0.4-1.0%, N: 0.3-0.6%, Co: 1.2%-2.0%, Cr: 4.0%-7.0%, Ni: 0.4%-1.2%, W: 2.0%-4.0%, Ti: 0.6%-1.0%, Mn: 0.6%-1.0%, Al: 0.5%-1.0%, Cu: 0.6%-1.2%, V: 1.5%-4.0%, S: 0.2%-0.8%, Mo: 5.0%-6.0%, Mg: 0.2%-0.8%, Nb: 0.5%-1.0%, Si: 0.4%-0.8%, toughening and cutting additives 2.0-4.0%, solid lubricant 0.8-1.2%, hard particles 0.8%-1.0%, balance Fe, particle size is 80-120 mesh.
[0012] Preferably, the toughening and cutting additive is TWIP steel, whose chemical composition is: C: 0.6-1.2%, Mn: 18.0%-24.0%, Al: 1.0%-3.0%, Si: 0.5%-1.5%, Ni: 0.3%-0.8%, Cr: 0.3%-0.6%, the balance is Fe, and the particle size is 80-120 mesh. Preferably, the hard particles are one or both of WC and NTi.
[0013] Preferably, the solid lubricant is two or three of graphite, MnS, and MoS2.
[0014] Preferably, the coating is composed of a Ni transition layer with a thickness of 0.1-0.5 μm and a Cr / Ni functional coating with a thickness of 1.5-2.0 μm.
[0015] Another object of the present invention is to provide a preparation process of the above engine valve guide, and the specific preparation steps are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare powder. Screen out TWIP steel powder with a powder size of 80-120 mesh and use it as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders and metal powders in proportion to form alloy powder with a powder particle size of 80-120 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 60-120 minutes; the nitrogen element exists in the form of nitrogen or a compound; (3) Mold wall lubrication: Add 0.20% of mold wall lubricant by mass to lubricate the mold wall in the female mold cavity of the valve guide; (4) Warm pressing: Double-layer filling technology is used during pressing. During powder pressing, the negative template is floated twice and the powder is loaded twice to control the diffusion bonding and interface structure of the two powders during compaction, sintering and heat treatment. The powder is warm pressed at 150-180°C and a pressure of 600MPa-800MPa. (5) Sintering: The formed valve guide green body is placed in a push rod furnace, and the valve guide green body is manufactured by a 4-stage pre-sintering + 3-stage sintering method under N2 as a protective atmosphere, wherein the pre-sintering temperature is 650-700°C and the time is 1-2 hours; the three-stage sintering is as follows: the first sintering is performed at 780-800°C for 1.0-2.0 hours, the second sintering is performed at 800-900°C for 1.0-2.0 hours, and the last sintering is performed at 1150°C-1200°C for 1.0-2.0 hours. After the sintering is completed, the green body is naturally cooled to obtain the desired sintered product; (6) Siphon copper infiltration: During the sintering process, siphon copper infiltration is used to make liquid copper melt into the product along the micropores, filling the holes and improving the density, thermal conductivity and strength of the product; (7) Heat treatment: The cooled sintered product is placed in a box furnace for heat treatment. The heat treatment process is to keep the product at a temperature of 880-900°C for 1.0-2.0h, then quench it, and then keep it at a tempering temperature of 240-280°C for 1.0-2.0h in the furnace for cooling. (8) Finishing: Use CNC machine tools to finish the valve guide; (9) Magnetron sputtering transition layer: The transition layer is prepared by magnetron sputtering technology. Ar is used as the protective gas for magnetron sputtering, the target material is Ni, the distance between the target material and the valve guide substrate is 80-100 mm, the deposition pressure is 0.1-1.0 Pa, the target bias voltage is 400-800 V, and the target current density is 5-10 mA / cm 2 , power density is 5-20W / cm 2 , the deposition rate is 200-500nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.1-0.5μm; (10) Magnetron sputtering functional coating: The functional coating is prepared by magnetron sputtering technology. Ar is used as the protective gas for magnetron sputtering. The target material is Cr / Ni. The distance between the target material and the valve guide substrate is 80-100 mm. The deposition pressure is 0.1-1.0 Pa. The target bias voltage is 300-1000 V. The target current density is 5-10 mA / cm 2 , power density is 5-20W / cm 2, the deposition rate is 300-600nm / min, the working temperature is 200℃, and the thickness of the Cr / Ni functional coating is 1.5-2.0μm.
[0016] Preferably, the lubricant in step (3) is Zn[CH3(CH2) 16 CO0]2.
[0017] Preferably, in the siphon copper infiltration in step (6), the copper infiltration temperature is 1100-1200° C. and the copper infiltration time is 0.5-2 h.
[0018] Preferably, the valve guide obtained by the above preparation process has a density of 8.0 g / cm 3 Above, tensile strength is 750-800MPa, impact toughness is 10-13J / cm 2 , hardness ≥ HRC53, crushing strength after heat treatment ≥ 1250MPa, valve sinking after 1000h of wear-resistant bench test at 1000℃ is 80-100μm, interference ≤ 80μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is ≤15μm, the oxidation weight gain rate is ≤0.06%; the vulcanization weight gain rate is ≤0.60%.
[0019] Another object of the present invention is to provide the application of the above-mentioned engine valve guide in the preparation of engine accessories including but not limited to hydrogen, natural gas, LPG gas, oil-gas hybrid power, and fuel.
[0020] Compared with the existing powder metallurgy valve guide technology for engines, the beneficial effects of the present invention are: 1. Aiming at the working environment and required working performance of the valve guide, the present invention re-studies and designs an Fe-based powder metallurgy material composition. The alloy powder contains elements such as C, N, Co, Cr, Ni, W, Ti, Mn, Al, Cu, V, S, Mo, Mg, Nb and Si, which significantly improves the strength, hardness, toughness, wear resistance, high temperature performance and corrosion resistance of the Fe-based alloy.
[0021] Since solid solution strengthening and martensite / carbide / precipitation phase strengthening are the most common strengthening and hardening mechanisms of Fe-based alloys, in order to ensure that Fe-based alloys still have high toughness and hardness at high temperatures, special alloying elements and their contents must be selected to form stable martensite and carbide hard phases at high temperatures. The present invention obtains an alloy matrix with solid solution / martensitic phase transformation / dispersion strengthening characteristics through multi-component alloying of C, Cr, Ni, Mo and W and microalloying and post-treatment processes of elements such as V, Ti and Nb, wherein higher C, Cr, Ni and Mo contents will increase the solid solution amount of alloying elements in the martensitic phase, and combined with the addition of W, complex carbides containing Cr and W can be formed, thereby simultaneously improving the hardness and high temperature stability of the martensitic matrix and carbides, and through the addition of elements such as V, Ti and Nb, it is intended to form a high-hardness dispersed precipitation phase to further improve the overall hardness of the matrix.
[0022] The Fe-based alloy matrix component of the present invention can make the valve guide have higher hardness, toughness, wear resistance, good high temperature performance and corrosion resistance, etc. The valve guide product produced has obvious technical advantages compared with existing products.
[0023] 2. The present invention uses TWIP steel powder as a toughening and cutting additive, which well balances the technical contradiction between the wear resistance and cutting processability of high-hardness materials.
[0024] 3. After the valve guide is pressed into powder, sintered and heat treated, it must be cut and then press-fitted with the cylinder body. However, the high hardness and high wear resistance of the material often result in poor cutting performance of the product. During press-fitting, an alarm is often sounded due to excessive pressure, resulting in the product being scrapped.
[0025] In order to solve the technical contradiction between high hardness and processing performance, the present invention adds an appropriate amount of TWIP steel powder to the base material. TWIP steel is a new type of high-alloy steel with outstanding plasticity and toughness. Its extremely high plasticity and low hardness are used to improve the cutting processing performance of the base material. At the same time, its outstanding work hardening characteristics are used to increase its own hardness when the valve guide is subjected to impact to offset the effect of its addition on the overall hardness of the material, thereby obtaining a composite material with both wear resistance and cutting processing properties.
[0026] 3. The technology of warm pressing + die wall lubrication is adopted to make the density of sintered powder metallurgy valve guide reach 8.0 g / cm 3 The above ensures that the valve guide has high strength, hardness and wear resistance.
[0027] 4. Carbon / nitrogen compounds are industrial ceramic materials with high stability and hardness, among which typical carbides include Cr7C3, WC, etc., and typical nitrides include NTi, SiN, etc. The present invention obtains in-situ self-generated (Cr, Fe)7C3 type carbides by designing the Cr / C ratio of the matrix; introduces hard particles by adding WC and NTi, and improves the wettability of the hard particles and the Fe matrix by surface treatment process; and forms a good metallurgical bond between the hard phase particles and the matrix by high-temperature sintering, thereby obtaining good wear resistance.
[0028] 5. The use of advanced technologies such as double-layer filler technology, multi-stage temperature zone sintering technology and siphon copper infiltration technology ensures the excellent performance of valve guide products such as hardness, toughness, wear resistance and high temperature resistance.
[0029] 6. The valve guide of the present invention has a tensile strength of 750-780 MPa and an impact toughness of 10-13 J / cm 2 , hardness ≥HRC53, so it has the characteristics of easy cutting and high wear resistance.
[0030] 7. The valve guide of the present invention has a crushing strength of ≥1250MPa after heat treatment, a valve sinking amount of 80-100μm after 1000h of wear-resistant bench test at 1000℃, an interference amount of ≤80μm, and an engine bench test at 8×10 5 After reciprocating times, the wear loss is ≤15μm, the oxidation weight gain rate is ≤0.06%, and the vulcanization weight gain rate is ≤0.60%, so it has excellent performance of high temperature resistance and high wear resistance.
[0031] 8. The valve guide of the present invention adopts magnetron sputtering technology to prepare the transition Ni layer and the functional Cr / Ni coating, which can further improve the hardness, strength, wear resistance, corrosion resistance, and resistance to hydrogen embrittlement and hydrogen corrosion of the working surface of the valve guide.
[0032] Therefore, the valve guide prepared by the present invention has excellent density, high corrosion resistance, high wear resistance and good high temperature performance, and is easy to cut, resistant to hydrogen embrittlement and hydrogen corrosion, and can be used for working conditions including but not limited to hydrogen, natural gas (CNG, LNG), LPG gas, oil and gas hybrid power, and fuel engines under high temperature, dry friction, impact, gas corrosion and other service conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The figure is a metallographic structure diagram of a valve guide made of the material of the present invention after sintering.
[0034] Figure 2 It is a metallographic structure diagram of the valve guide made of the material of the present invention after heat treatment (quenching + tempering state).
[0035] in, Figure 1The sintered microstructure shown is mainly composed of pearlite, a small amount of martensite and carbides; Figure 2 The microstructure after heat treatment is tempered troostite, pearlite and dispersed carbide particles. This composite strengthening structure not only meets the strength, hardness and density requirements of the valve guide, but also has certain plasticity, impact toughness, high temperature wear resistance and corrosion resistance, and has excellent comprehensive performance. DETAILED DESCRIPTION
[0036] In order to better illustrate the technical content, technical features, application scenarios, etc. of the valve guide of the present invention, the following implementation examples include but are not limited to the present invention.
[0037] Example 1 The engine valve guide is made of an Fe-based alloy substrate and a coating is applied on the working surface by a magnetron sputtering process.
[0038] Among them, the Fe-based alloy matrix is composed of the following components in proportion by mass: C: 0.6%, N: 0.4%, Co: 1.2%, Cr: 5.0%, Ni: 0.6%, W: 3.0%, Ti: 0.6%, Mn: 0.6%, Al: 0.6%, Cu: 0.8%, V: 2.5%, S: 0.4%, Mo: 5.0%, Mg: 0.6%, Nb: 0.6%, Si: 0.8%, 2.0% toughening and cutting additives, 0.8% hard particles, 1.2% solid lubricant, and the remainder Fe, with a particle size of 80 mesh.
[0039] Among them, the toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.6%, Mn: 18%, Al: 1.8%, Si: 0.6%, Ni: 0.4%, Cr: 0.4%, the remainder is Fe, and the particle size is 80 mesh.
[0040] The hard particles are WC. The solid lubricants are graphite and MnS, with a mass ratio of 50%:50% respectively.
[0041] The coating consists of a Ni transition layer with a thickness of 0.1 μm and a Cr / Ni functional coating layer with a thickness of 1.5 μm, and is prepared using magnetron sputtering technology.
[0042] The specific preparation steps of the above engine valve guide are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare powder. Screen out TWIP steel powder with a powder size of 80 mesh and use it as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 80 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 60 minutes; (3) Mold wall lubrication: Add 0.20% of mold wall lubricant to lubricate the mold wall in the female mold cavity of the valve guide. The lubricant is Zn[CH3(CH2) 16 CO0]2; (4) Warm pressing: Double-layer filling technology is used during pressing. During powder pressing, the negative template is floated twice and the powder is loaded twice. The powder is warm pressed at 150°C and a pressure of 700MPa. (5) Sintering: The formed valve guide green body is placed in a push rod furnace and manufactured by a 4-stage pre-sintering + 3-stage sintering method under N2 as a protective atmosphere, wherein the pre-sintering temperature is 650°C and the time is 1 h. The three stages of sintering are: the first sintering is performed at 780°C for 1.0 h, the second sintering is performed at 800°C for 1.0 h, and the last sintering is performed at 1150°C for 1.0 h. After sintering, the green body is naturally cooled; (6) Siphon copper infiltration: During the sintering process, the siphon copper infiltration technology is used to make the liquid copper melt into the product along the micropores, fill the holes, and improve the density, thermal conductivity and strength of the product; (7) Heat treatment: Heat treatment is carried out in a box furnace, and the steel is quenched after being kept at 880°C for 1.0 h, and then kept at the tempering temperature of 250°C for 1.0 h and furnace cooled; (8) Finishing: Use CNC machine tools to finish the valve guide; (9) Magnetron sputtering transition layer: The transition layer was prepared using magnetron sputtering technology. Ar was used as the protective gas, the target material was Ni, the distance between the target material and the valve guide substrate was 80 mm, the deposition pressure was 0.2 Pa, the target bias voltage was 400 V, and the target current density was 5 mA / cm 2 , power density is 5W / cm 2 , the deposition rate is 200nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.1μm; (10) Magnetron sputtering functional coating: The functional coating was prepared using magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering. The target material was Cr / Ni. The distance between the target material and the valve guide substrate was 80 mm. The deposition pressure was 0.1 Pa. The target bias voltage was 400 V. The target current density was 5 mA / cm 2 , power density is 5W / cm 2 , the deposition rate is 300nm / min, the working temperature is 200℃, and the thickness of the Cr / Ni functional coating is 1.5μm.
[0043] After testing, the valve guide density is 8.05g / cm 3 , tensile strength is 760MPa, impact toughness is 10.9J / cm 2 , hardness is 54HRC, crushing strength is 1290MPa, at 1000℃, after 1000h of engine bench test, its sinking amount is 80μm, interference is 80μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 10μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0044] Example 2 The engine valve guide is made of an Fe-based alloy substrate and a coating is applied on the working surface by a magnetron sputtering process.
[0045] Among them, the Fe-based alloy matrix is composed of the following components in proportion by mass: C: 0.8%, N: 0.4%, Co: 1.5%, Cr: 4.0%, Ni: 0.8%, W: 3.5%, Ti: 0.8%, Mn: 0.7%, Al: 0.8%, Cu: 1.0%, V: 2.0%, S: 0.3%, Mo: 6.0%, Mg: 0.5%, Nb: 0.5%, Si: 0.6%, 3.0% toughening and cutting additives, 0.8% hard particles, 1.2% solid lubricants, and the remainder Fe, with a particle size of 100 mesh.
[0046] The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.8%, Mn: 20%, Al: 1.2%, Si: 0.8%, Ni: 0.5%, Cr: 0.5%, the balance is Fe, and the particle size is 100 mesh.
[0047] The hard particles are NTi. The solid lubricants are MnS and MoS2, with a mass ratio of 50%:50% respectively.
[0048] The coating consists of a Ni transition layer with a thickness of 0.3 μm and a Cr / Ni functional coating with a thickness of 1.5 μm.
[0049] The specific preparation steps of the above engine valve guide are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare powder. Screen out TWIP steel powder with a powder size of 100 mesh and use it as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 100 mesh; (3) Warm pressing: Double-layer filling technology is used during pressing. During powder pressing, the negative template is floated twice and the powder is loaded twice. The powder is warm pressed at a temperature of 160°C and a pressure of 750MPa. (4) Sintering: The formed valve guide green body is placed in a push rod furnace and manufactured by a 4-stage pre-sintering + 3-stage sintering method under N2 as a protective atmosphere, wherein the pre-sintering temperature is 680°C and the time is 1 h; the three-stage sintering is as follows: the first sintering is at 800°C for 2.0 h, the second sintering is at 860°C for 2.0 h, and the last sintering is at 1180°C for 2.0 h, and then naturally cooled after sintering; (5) Siphon copper infiltration: During the sintering process, the siphon copper infiltration technology is used to make the liquid copper melt into the product along the micropores, fill the holes, and improve the density, thermal conductivity and strength of the product; (6) Heat treatment: Heat treatment is carried out in a box furnace, at a temperature of 880°C for 2.0 h, then quenching, and then at a tempering temperature of 260°C for 2.0 h, followed by furnace cooling; (7) Finishing: Use CNC machine tools to finish the valve guide; (8) Magnetron sputtering transition layer: The transition layer was prepared using magnetron sputtering technology. Ar was used as the protective gas, the target material was Ni, the distance between the target material and the valve guide substrate was 90 mm, the deposition pressure was 0.5 Pa, the target bias voltage was 600 V, and the target current density was 8 mA / cm 2 , power density is 10W / cm 2 , the deposition rate is 300nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.3μm; (9) Magnetron sputtering functional coating: The functional coating was prepared using magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering. The target material was Cr / Ni. The distance between the target material and the valve guide substrate was 90 mm. The deposition pressure was 0.5 Pa. The target bias voltage was 700 V. The target current density was 8 mA / cm 2 , power density is 10W / cm 2 , the deposition rate is 400nm / min, the working temperature is 200℃, and the thickness of the Cr / Ni functional coating is 1.5μm.
[0050] After testing, the valve guide density is 8.1g / cm 3 , tensile strength is 770MPa, impact toughness is 11.1J / cm 2 , hardness is 55HRC, crushing strength is 1300MPa, at 1000℃, after 1000h of engine bench test, its sinking amount is 80μm, interference is 80μm, engine bench 8×10 5After two reciprocating strokes, the wear loss is 15μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0051] Example 3 The engine valve guide is made of an Fe-based alloy substrate and a coating is applied on the working surface by a magnetron sputtering process.
[0052] Among them, the Fe-based alloy matrix is composed of the following components in proportion by mass: C: 0.9%, N: 0.6%, Co: 1.8%, Cr: 7.0%, Ni: 1.2%, W: 4.0%, Ti: 0.9%, Mn: 0.8%, Al: 0.8%, Cu: 0.8%, V: 4.0%, S: 0.8%, Mo: 6.0%, Mg: 0.8%, Nb: 0.5%, Si: 0.4%, 4.0% toughening and cutting additives, 1.0% hard particles, 1.2% solid lubricant, balance Fe, particle size is 120 mesh.
[0053] The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 1.0%, Mn: 23.0%, Al: 1.5%, Si: 1.2%, Ni: 0.8%, Cr: 0.6%, the balance is Fe, and the particle size is 120 mesh.
[0054] The hard particles are WC. The solid lubricants are graphite and MoS2, accounting for 50% and 50% respectively.
[0055] The coating consists of a Ni transition layer with a thickness of 0.5 μm and a Cr / Ni functional coating with a thickness of 2.0 μm.
[0056] The specific preparation steps of the above engine valve guide are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare powder. Screen out TWIP steel powder with a powder size of 120 mesh and use it as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 120 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 90 minutes; (3) Mold wall lubrication: Add 0.20% of mold wall lubricant to lubricate the mold wall in the negative mold cavity of the valve guide. The lubricant is Zn[CH3(CH2) 16 CO0]2; (4) Warm pressing: Double-layer filling technology is used during pressing. During powder pressing, the negative template is floated twice and the powder is loaded twice. The powder is warm pressed at a temperature of 180°C and a pressure of 800MPa. (5) Sintering: The formed valve guide green body is placed in a push rod furnace and manufactured by a 4-stage pre-sintering + 3-stage sintering method under N2 as a protective atmosphere. The pre-sintering temperature is 700°C and the time is 2 h. The three stages of sintering are: the first sintering is at 800°C for 1.5 h, the second sintering is at 900°C for 2.0 h, and the last sintering is at 1200°C for 2.0 h. After sintering, it is naturally cooled; (6) Siphon copper infiltration: Siphon copper infiltration technology is used during the sintering process; (7) Heat treatment: Heat treatment is carried out in a box furnace, at a temperature of 900°C for 2.0 h, then quenching, and then at a tempering temperature of 280°C for 2.0 h, followed by furnace cooling; (8) Finishing: Use CNC machine tools to finish the valve guide; (9) Magnetron sputtering transition layer: The transition layer was prepared using magnetron sputtering technology. Ar was used as the protective gas, the target material was Ni, the distance between the target material and the valve guide substrate was 100 mm, the deposition pressure was 1 Pa, the target bias voltage was 800 V, and the target current density was 10 mA / cm 2 , power density is 20W / cm 2 , the deposition rate is 500nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.5μm; (10) Magnetron sputtering functional coating: The functional coating was prepared using magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering. The target material was Cr / Ni. The distance between the target material and the valve guide substrate was 100 mm. The deposition pressure was 1 Pa. The target bias voltage was 1000 V. The target current density was 10 mA / cm 2 , power density is 20W / cm 2 , the deposition rate is 600nm / min, the working temperature is 200℃, and the thickness of the Cr / Ni functional coating is 2.0μm; After testing, the valve guide density is 8.05g / cm 3 , tensile strength is 750MPa, impact toughness is 11.4J / cm 2 , hardness is 54HRC, crushing strength is 1270MPa, at 1000℃, after 1000h of engine bench test, its sinking amount is 90μm, interference is 70μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 10μm, the oxidation weight gain rate is 0.05%; the vulcanization weight gain rate is ≤0.5%.
[0057] Comparative Example 1 The comparative example 1 is opposite to the embodiment 1, and the difference is that the content of the toughening and cutting additive in the comparative example 1 is 0.
[0058] After testing, the valve guide density is 7.65g / cm 3 , tensile strength is 720MPa, impact toughness is 9.8J / cm 2 , hardness is 52HRC, crushing strength is 1240MPa, at 1000℃, after 1000h of engine bench test, its sinking amount is 70μm, interference is 62μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is 20μm, the oxidation weight gain rate is 0.08%; the vulcanization weight gain rate is ≤0.7%.
[0059] It can be seen from Examples 1-3 and Comparative Example 1 that the present invention can effectively improve the hardness and easy cutting degree of the valve guide material of the present invention and reduce the wear of the material by adding the toughening and easy cutting additive. As the content of the toughening and easy cutting additive increases, the tensile strength of the valve guide material first increases significantly and then decreases, the impact toughness continues to increase, and the wear first increases and then decreases.
Claims
1. An engine valve guide, characterized in that: It is made of Fe-based alloy substrate and coated on its working surface by magnetron sputtering process. Among them, the Fe-based alloy matrix is composed of the following components in proportion by mass: C: 0.4-1.0%, N: 0.3-0.6%, Co: 1.2%-2.0%, Cr: 4.0%-7.0%, Ni: 0.4%-1.2%, W: 2.0%-4.0%, Ti: 0.6%-1.0%, Mn: 0.6%-1.0%, Al: 0.5%-1.0%, Cu: 0.6%-1.2%, V: 1.5%-4.0%, S: 0.2%-0.8%, Mo: 5.0%-6.0%, Mg: 0.2%-0.8%, Nb: 0.5%-1.0%, Si: 0.4%-0.8%, toughening and cutting additives 2.0-4.0%, solid lubricant 0.8-1.2%, hard particles 0.8%-1.0%, balance Fe, particle size is 80-120 mesh.
2. The engine valve guide according to claim 1, characterized in that: The toughening and cutting additive is TWIP steel, and its chemical composition is: C: 0.6-1.2%, Mn: 18.0%-24.0%, Al: 1.0%-3.0%, Si: 0.5%-1.5%, Ni: 0.3%-0.8%, Cr: 0.3%-0.6%, the balance is Fe, and the particle size is 80-120 mesh.
3. The engine valve guide according to claim 1, characterized in that: The hard particles are one or two of WC and NTi.
4. The engine valve guide according to claim 1, characterized in that: The solid lubricant is two or three of graphite, MnS and MoS2.
5. The engine valve guide according to claim 1, characterized in that: The coating consists of a Ni transition layer with a thickness of 0.1-0.5 μm and a Cr / Ni functional coating layer with a thickness of 1.5-2.0 μm, and is prepared by using magnetron sputtering technology.
6. The process for preparing an engine valve guide according to any one of claims 1 to 5, characterized in that: The specific preparation steps are as follows: (1) Preparation of toughening and cutting additives: Prepare raw materials according to the composition ratio, use electric arc furnace smelting to prepare TWIP steel, and use aerosol method to prepare powder. Screen out TWIP steel powder with a powder size of 80-120 mesh and use it as a toughening and cutting additive; (2) Mixing powder: Mix different metal powders in proportion to form alloy powder with a powder particle size of 80-120 mesh, add toughening and cutting additives, hard particles and solid lubricants, and dry mix on a mixer for 60-120 minutes; (3) Mold wall lubrication: Add 0.20% of mold wall lubricant by mass to lubricate the mold wall in the female mold cavity of the valve guide; (4) Warm pressing: Double-layer filling technology is used during pressing. During powder pressing, the negative template is floated twice and the powder is loaded twice to control the diffusion bonding and interface structure of the two powders during compaction, sintering and heat treatment. The powder is warm pressed at 150-180°C and a pressure of 600MPa-800MPa. (5) Sintering: The formed valve guide green body is placed in a push rod furnace, and the valve guide green body is manufactured by a 4-stage pre-sintering + 3-stage sintering method under N2 as a protective atmosphere, wherein the pre-sintering temperature is 650-700°C and the time is 1-2 hours; the three-stage sintering is as follows: the first sintering is performed at 780-800°C for 1.0-2.0 hours, the second sintering is performed at 800-900°C for 1.0-2.0 hours, and the last sintering is performed at 1150°C-1200°C for 1.0-2.0 hours. After the sintering is completed, the green body is naturally cooled to obtain the desired sintered product; (6) Siphon copper infiltration: During the sintering process, siphon copper infiltration is used to make liquid copper melt into the product along the micropores, filling the holes and improving the density, thermal conductivity and strength of the product; (7) Heat treatment: The cooled sintered product is placed in a box furnace for heat treatment. The heat treatment process is to keep the product at a temperature of 880-900°C for 1.0-2.0h, then quench it, and then keep it at a tempering temperature of 240-280°C for 1.0-2.0h in the furnace for cooling. (8) Finishing: Use CNC machine tools to finish the valve guide; (9) Magnetron sputtering transition layer: The Ni transition layer was prepared by magnetron sputtering technology. Ar was used as the protective gas for magnetron sputtering, the target material was Ni, the distance between the target material and the valve guide substrate was 80-100 mm, the deposition pressure was 0.1-1.0 Pa, the target bias voltage was 400-800 V, and the target current density was 5-10 mA / cm 2 , power density is 5-20W / cm 2 , the deposition rate is 200-500nm / min, the working temperature is 200℃, and the Ni transition layer thickness is 0.1-0.5μm; (10) Magnetron sputtering functional coating: Cr / Ni functional coating is prepared by magnetron sputtering technology. Ar is used as the protective gas for magnetron sputtering. The target material is Cr / Ni. The distance between the target material and the valve guide substrate is 80-100 mm. The deposition pressure is 0.1-1.0 Pa. The target bias voltage is 300-1000 V. The target current density is 5-10 mA / cm 2 , power density is 5-20W / cm 2 , the deposition rate is 300-600nm / min, the working temperature is 200℃, and the thickness of the Cr / Ni functional coating is 1.5-2.0μm.
7. The process for preparing an engine valve guide according to claim 6, wherein the lubricant in step (3) is Zn[CH3(CH2) 16 CO0]2.
8. The process for preparing an engine valve guide according to claim 6, wherein the siphon copper infiltration in step (6) has a copper infiltration temperature of 1100-1200°C and a copper infiltration time of 0.5-2 hours.
9. The process for preparing an engine valve guide according to any one of claims 6 to 8, characterized in that: The density of the valve guide obtained by the above preparation process reaches 8.0 g / cm 3 Above, tensile strength is 750-800MPa, impact toughness is 10-13J / cm 2 , hardness ≥ HRC53, crushing strength after heat treatment ≥ 1250MPa, valve sinking after 1000h of wear-resistant bench test at 1000℃ is 80-100μm, interference ≤ 80μm, engine bench 8×10 5 After two reciprocating strokes, the wear loss is ≤15μm, the oxidation weight gain rate is ≤0.06%; the vulcanization weight gain rate is ≤0.60%.
10. Use of the engine valve guide according to any one of claims 1 to 5 in the preparation of engine accessories including but not limited to hydrogen, natural gas, LPG gas, oil-gas hybrid power, and fuel oil.
Citation Information
Cited By
High-performance powder metallurgy alloy, engine valve seat ring and preparation method of engine valve seat ring
CN121472727A